2018
DOI: 10.1007/s10212-018-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive flexibility in young children’s potential for learning under dynamic testing conditions

Abstract: The aim of the current study was to investigate to what extent children's potential for learning is related to their level of cognitive flexibility. Potential for learning was measured through a dynamic testing procedure that aimed to measure how much a child can profit from a training procedure integrated into the testing process, including the amount and type of feedback the children required during this training procedure. The study followed a pre-test-training-post-test control group design. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
1
11
0
3
Order By: Relevance
“…In a study by Wiedl et al (2004), in which adult psychiatric patients were administered a dynamic version of the WCST, for example, planning was associated more strongly with the post-test than with the pre-test. The participants were, however, With regard to the relationship between planning and instructional needs, it was found that the instructions children needed in the first training session only could be predicted by their planning abilities, with children with weaker planning skills requiring more prompts, as was also found in earlier research into different executive functions (Stad et al, 2018). These results likely reveal that planning abilities are only initially associated with need for instruction in a training or learning context, and that further learning experiences counter the influence of planning.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In a study by Wiedl et al (2004), in which adult psychiatric patients were administered a dynamic version of the WCST, for example, planning was associated more strongly with the post-test than with the pre-test. The participants were, however, With regard to the relationship between planning and instructional needs, it was found that the instructions children needed in the first training session only could be predicted by their planning abilities, with children with weaker planning skills requiring more prompts, as was also found in earlier research into different executive functions (Stad et al, 2018). These results likely reveal that planning abilities are only initially associated with need for instruction in a training or learning context, and that further learning experiences counter the influence of planning.…”
Section: Discussionmentioning
confidence: 68%
“…Executive functions are often considered to be a conglomerate of inter-related complex, general cognitive processes that enable control of thinking and behavior (Monette, Bigras, & Guay, 2011). Most of the studies in this field examined the role of working memory (e.g., Swanson, 2006;Stevenson, Heiser, & Resing, 2013), and, to a lesser extent, cognitive flexibility (Stad et al, 2018), and metacognition (Vogelaar et al, 2017). In general, it seems that, by providing children with feedback and help during training, dynamic testing facilitates children with weaker executive functions in showing their cognitive potential.…”
Section: Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive flexibility (CF) is a core executive function generally defined as the capacity to efficiently adjust behavior in response to changing situational demands [1]. In humans, CF confers a higher potential for learning in children [2] and predicts academic achievement in college students [3]. Furthermore, CF facilitates resilience to negative life events and everyday stress among adults [4], and is in turn impaired in adults exposed to early life stress [5].…”
Section: Introductionmentioning
confidence: 99%